Knowledge acquisition for knowledge-based engineering systems. (4th March 2005) - Preston, S.; Chapman, C.; Pinfold, M.; Smith, G.
This paper is essentially concerned with the development of formal representations of knowledge required prior to the development of knowledge-based engineering systems (KBESs). Initially, the paper provides a brief introduction to knowledge-based systems (KBSs) and KBESs, stating the key commonalities and differences between the two, and presents the three main types of KBES. The paper then focuses upon knowledge acquisition, and specifically on the use of the MOKA methodology to support knowledge acquisition for KBES development. The paper critically considers the structure of MOKA with respect to workflow. This work concludes that the methodology has certain weaknesses which require addressing before it can reach its full potential as a knowledge acquisition methodology for the development of KBESs.